Особливості мережі пасажирського транспорту міста Кривий Ріг - Монастирський, Юрій; Сістук, Володимир (Видавництво Львівської політехніки, 2018)
The recommendations for a rational public transport network`s configuration using large passengers capacity vehicles were developed and implemented based on public transport network routes classification in keeping with their allocation in the city and the degree of the duplication.
Features of the network of the passenger transport of the city of Kryvy Rig
Keywords: 656.015